Transformasi metodologi pendidikan Islam melalui integrasi PjBL dan Critical Pedagogy Islami - Ramadhan, Rizal Ilham; Mujahidin, Endin; Lisnawati, Santi (Program Studi Magister Pendidikan Agama Islam, 2026)
This research aims to develop an Islamic learning methodology design through the integration of Project-Based Learning (PjBL) with Islamic Critical Pedagogy. The study employed a literature review method with a descriptive qualitative approach, analyzing the theories, characteristics, and application of both approaches in the context of Islamic education. The results indicate that PjBL increases student engagement in solving real-world problems, while Islamic Critical Pedagogy fosters critical awareness grounded in spiritual values and etiquette. The integration of the two creates participatory, transformative learning that is relevant to the needs of the 21st century. The case study of